Theoretical studies of energy spectra and E1 transitions of Ni II ion. Issue 13 (January 2020) - Rynkun, P; Gaigalas, G; Jönsson, P
Synopsis: Accurate atomic data of the iron group elements are of major importance in astrophysics. In the present work energy spectrum calculations are performed for 332 lowest states for Ni II ion. Energy levels are compared with NIST database recommended values. All computations were done using the general-purpose relativistic atomic structure package GRASP2018.